Assessing Survey Items on Social Norms Relating to Dating and Relationship Violence and to Gender: Cognitive Interviews with Young People in England - Meiksin, Rebecca (Journal of interpersonal violence, 2024)
Widespread among adolescents in England, dating and relationship violence (DRV) is associated with subsequent injuries and serious mental health problems. While DRV prevention interventions often aim to shift harmful social norms, no established measures exist to assess relevant norms and their role in mediating DRV outcomes. We conducted cognitive interviews exploring the understandability and answerability of candidate measures of social norms relating to DRV and gender roles, informing measure refinement. In all, 11 participants aged 13 to 15 from one school in England participated. Cognitive interviews tested two items assessing descriptive norms (beliefs about what behaviors are typical), three assessing injunctive norms (beliefs about what is socially acceptable), and (for comparison) one assessing personal attitudes. Findings were summarized by drawing on interview notes. Summaries and interview notes were subjected to thematic analysis. For some participants, injunctive norms items required further explanation to clarify that items asked about others’ views, not their own. Lack of certainty about, and perceived heterogeneity of, behaviors and views among a broad reference group detracted from answerability. Participants were better able to answer items for which they could draw on concrete experiences of observing or discussing relevant behaviors or social sanctions. Data suggest that a narrowed reference group could improve answerability for items assessing salient norms. Findings informed refinements to social norms measures. It is possible to develop social norms measures that are understandable and answerable for adolescents in England. Measures should assess norms that are salient and publicly manifest among a cohesive and influential reference group.